The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s1519-69842002000500014
|View full text |Cite
|
Sign up to set email alerts
|

Biflagellate spermatozoon structure of the hermaphrodite fish Satanoperca jurupari (Heckel, 1840) (Teleostei, Cichlidae) from the Amazon River

Abstract: The ultrastructural features of the sperm were studied in the hermaphroditic teleost Satanoperca jurupari HECKEL, 1840 from Amazon River. Spermatocytes, spermatids and sperm develop in the testicular cysts among the different oocyte stages. Different stages of early spermatocyte development, mainly the ones with synaptonemal complexes were often observed. The mature spermatozoa belong to the introsperm type, with a short head (~ 3 µm long and 1.3 µm wide) without acrosome, short midpiece (~ 1.2 µm long and 1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
0
17
1
Order By: Relevance
“…According to Jamieson (1991) it has occurred at least six times in fishes. Recently, Matos et al (2002) described biflagellar tails in a cichlid fish, Satanoperca jurupari, not observed in testes of a larger group of species from the same family studied by Fishelson (2003a, b). According to these authors the sperm flagella in Satanoperca are separated, each bearing lateral cytoplasmic extensions (wings).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to Jamieson (1991) it has occurred at least six times in fishes. Recently, Matos et al (2002) described biflagellar tails in a cichlid fish, Satanoperca jurupari, not observed in testes of a larger group of species from the same family studied by Fishelson (2003a, b). According to these authors the sperm flagella in Satanoperca are separated, each bearing lateral cytoplasmic extensions (wings).…”
Section: Discussionmentioning
confidence: 92%
“…Studies by Franzen (1970), Mattei (1971Mattei ( , 1988, Billard (1986), Lashnsteiner and Patzner (1990), and Fishelson (2003a, b) revealed a diversified structure of the sperm and their tails (flagella) in various fish families. All these studies demonstrated that in most teleosts, as in other vertebrates, the sperm possess a single flagella, while only a few families, e.g., batrachids, bagrids, myctophids, gobiesocids, and more recently cichlids, contain species that have been found with biflagellar sperm (Mattei 1988;Matos et al 2002). The published studies enable comparison of the various components of the developing gametocytes, and consequent evolutionary considerations (Mattei 1988(Mattei , 1991.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, light microscopy and TEM revealed that they are biflagellate. To our knowledge, the only cichlid with biflagellate sperm described so far is Satanoperca jurupari, a self-fertilizing hermaphrodite with introsperm-type spermatozoa (Matos et al 2002). The existence of two flagella is even more exceptional among cichlids.…”
Section: Discussionmentioning
confidence: 98%
“…Often, the plasma membrane also forms one or two fin-like ridges along the fish sperm flagellar tail, which are oriented along the horizontal axis defined by the central microtubules [34][35][36][37]. The ribbon shape instead of the usual cylindrical shape of the flagellum makes it brighter when observed by dark-field microscopy and allows to better visualization and recording of wave shapes [6].…”
Section: Structure Of Fish Spermatozoamentioning
confidence: 99%